Rediscovery of Gryon chrysolaum (Walker) (Hymenoptera: Platygastridae)—an egg parasitoid of Holhymenia rubiginosa Breddin and Anisoscelis foliacea Fabricius (Heteroptera: Coreidae) - Polaszek, Andrew; Kolberg, Roberta (Zootaxa, 2008)
During surveys of natural enemies of the leaf-footed bugs Holhymenia rubiginosa Breddin and Anisoscelis foliacea Fabricius in Rio Grande do Sul State, Brazil, two species of primary egg parasitoids belonging to the genus Gryon were reared from these hosts. One of these Gryon species was identified as G. chrysolaum Walker, a species unknown since its description nearly 170 years ago. The second Gryon species reared was G. vitripenne Masner. These rearings represent the first host records for this species. Levels of parasitism by G. chrysolaum were 35% and 53% on H. rubiginosa and A. foliacea respectively. Additional specimens reared were a Neorileya and a Telenomus species. After examination of unidentified Gryon specimens in the Natural History Museum, London, a further three specimens were located, from Brazil and Mexico. Data on hosts and localities of all known specimens of G. chrysolaum are presented, and the species is redescribed and compared with its closest known relatives. The female is described for the first time.